A hibrid approach in first course of statistics - Morales Arsenal, Roberto (Pi-InnovaMath, 2019)
At the moment an intense debate is taking place on the form in which we teach in the classrooms in the different educational levels facing two conceptions: the traditional one against the innovative one. The debate about what and how to teach takes on special relevance when we teach quantitative subjects in careers with a nonquantitative profile such as Business Administration degree and with academic curricula that have gone from five to four years. Additionally, we must also add that the current student arrive at university with new psycho-social characteristics make the traditional tools available to us obsolete, this inevitably means that we have to adapt to the new framework. For this, we propose a design of the classes based on a combination of: 1) a set of traditional strategies and materials, 2) a set of multimedia tools 3) a set of learning techniques based on the concepts of neuroscience (neuroeducation) and finally 4) the implementation of flipped classroom. The empirical results show: with regard to students: 1) better average grade, 2) lower variability grades and professors received better general assessments at the end of the course about the dynamics of the class.